Memoria Histórica y Prácticas Comunicativas de la Tradición “El Animero”, en la Parroquia de Bayushig Provincia de Chimborazo - Arias Toapanta, Fausto Francisco (2017)
The parish of Bayushig province of Chimborazo, has traditions prevailing in the specification and practice of its inhabitants. One of the more important in the village, cultural representations is the tradition of animero, held every year, fifteen days before the celebration of the Day of the Dead, on November 2. Such funeral celebration has cultural and communicative practices. This, begins inside the cemetery Bayushig at midnight from October 24 to November 2. It is led by a man known as the "animero". This person is dressed in white robes and carrying a bell in his hands and a skull. A loudly proclaims "awaken sleeping souls, to pray three Our Father and three Hail Mary, blessed by the holy souls in purgatory"; walks accompanied the souls of the cemetery through the neighborhoods of the town. Research tradition seeks to answer what is the true origin of the tradition of animero?, because there is no tangible record evidencing the origin of the tradition, which has led to a lack of knowledge on children and youth of the parish. Reference was taken as the theoretical foundation of communication, cultural practices and customs allowing to know habits that are part of the inhabitants of Bayushig. The main objective is to present the historical transformations occurred in the religious celebration, customs, legends and myths, the animero. It concludes showing the ignorant religious and the low participation of youth in the religious tradition by social and cultural changes.